Paradigm shift in international economic law rule-making: TPP as a new model for trade agreements? - CHAISSE, Julien (Institutional Knowledge at Singapore Management University, 2017)
The TPP was negotiated among 12 economically diverse countries, including some most highly developed and rich countries (i.e., the United States, Japan, Australia, Canada, New Zealand, and Singapore), some newly industrialized countries (i.e., Mexico and Malaysia), and some less-developed countries (i.e., Peru, Chile, and Vietnam).